Dural Contact to the Malleus Head in Patients with Superior Semicircular Canal Dehiscence (SSCD): Case Series and Review of SSCD and Tegmen Defects. (December 2021) - Wentland, Carissa; Cousins, Joseph; May, Jason; Rivera, Arnaldo
Objective: Report a series of cases in which patients have concomitant superior semicircular canal dehiscence (SSCD) and a dehiscent tegmen tympani with Dural contact to the malleus head (DCMH). Methods: An analysis of radiologic and audiologic data in 4 patients who presented with SSCD and DCMH at a tertiary care institution. A pertinent literature review was performed. Results: Four patients (5 ears) had SSCD and DCMH. In 3 patients with unilateral DCMH, the mean maximum air-bone gap was 15 dB in the ear with DCMH compared to 50 dB in the ear without DCMH. Of the 5 ears with DCMH, the mean air conduction threshold at 250 Hz was 17 dB compared to 42 dB in the 3 ears without DCMH. Conclusions: We report the findings of DCMH in a series of 4 patients with bilateral SSCD. This limited series suggests that ears with SSCD and DCMH have less of an air-bone gap than would be expected, as 1 would expect an additive effect of DCMH and SSCD on the air-bone gap.